THE EVOLUTION OF PEDAGOGY: “FROM TRADITIONAL TO PROGRESSIVE METHODS” (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article analyzes the process of transition of pedagogy from traditional methods to progressive methods. As the educational system is constantly evolving, pedagogical approaches are also adapting to the needs of the times. While traditional pedagogy methods have been more teacher-centered, progressive approaches tend to be learner-centered. The article covers such issues as encouraging student activity, using interactive methods, and the importance of technology. The introduction of new pedagogical technologies is emphasized for the future development of pedagogy.